Abu Ubaid's Thoughts On Taxes and Zakat: Relevance Approach In Indonesia - Huda, Miftahul; Wahyu Santika, Bunga; Septi Purnamasari, Dian; Lukman Nugraha, Ahmad (Al-Qardhu, 2023)
This researcher discusses Abu Ubaid's concept of thinking about Taxes and Zakat, and its relevance to be providing solutions to the level of community welfare. Indonesia as a country with Muslim as a majority on his population, has a high potential for collecting zakat and be any of sources the state income. This study aims to examine more deeply the concept of public finance, especially regarding zakat and taxes from Abu Ubaid's perspective, and examine public finance in Indonesia. The method used is qualitative with a library study approach or library research, the primary source used in this study is the book of Al Amwal by Abu Ubaid. The results from this analysis is Abu Ubaid's concept of jizyah, kharaj, ushr, and various kinds of zakat being the solution and the concept of public finance, such he has described in Al Amwal's book. Researchers also try to analyze the tax concept that exists in Indonesia and the current contemporary zakat system. There are several things that can be concluded in this study that the capitalist system with various kinds of taxes applied in Indonesia it's been quite burdensome for the community, and the concept of zakat and its contemporary implementation become the solution for community welfare. Good management and funds are required and needed for zakat improvement.